Exact Solutions Involving two Jacobi Elliptic Functions for General Boussinesq Equation - Joseph, S. P. (Journal of Environmental Accounting and Management, 2026)
In this paper, several new exact traveling wave solutions for a general Boussinesq equation are derived. Boussinesq equation is a fourth order nonlinear partial differential equation which is used to study dynamics of water waves in fluid dynamics and other physical phenomena such as the dynamics of thin inviscid layers, non-linear lattice waves and vibration in nonlinear strings. We derive all the exact solutions which are the linear combinations of square of two Jacobi elliptic functions and a constant term. Since the computations are much more involved, required solutions are obtained using computer algebra system.